Self-assembly of H2S-responsive nanoprodrugs based on natural rhein and geraniol for targeted therapy against Salmonella Typhimurium - Lu Han; Tao Zang; Lulu Tan; Dunsheng Liang; Tengfei Long; Xuwei Liu; Xiaofan Shen; Hao Ren; ZhiPeng Li; Zhaoxiang Lu; Shengqiu Tang; Xiaoping Liao; et al. (Journal of Nanobiotechnology, 2023)
Abstract Salmonellosis is a globally extensive food-borne disease, which threatens public health and results in huge economic losses in the world annually. The rising prevalence of antibiotic resistance in Salmonella poses a significant global concern, emphasizing an imperative to identify novel therapeutic agents or methodologies to effectively combat this predicament. In this study, self-assembly hydrogen sulfide (H2S)-responsive nanoprodrugs were fabricated with poly(α-lipoic acid)-polyethylene glycol grafted rhein and geraniol (PPRG), self-assembled into core–shell nanoparticles via electrostatic, hydrophilic and hydrophobic interactions, with hydrophilic exterior and hydrophobic interior. The rhein and geraniol are released from self-assembly nanoprodrugs PPRG in response to Salmonella infection, which is known to produce hydrogen sulfide (H2S). PPRG demonstrated stronger antibacterial activity against Salmonella compared with rhein or geraniol alone in vitro and in vivo. Additionally, PPRG was also able to suppress the inflammation and modulate gut microbiota homeostasis. In conclusion, the as-prepared self-assembly nanoprodrug sheds new light on the design of natural product active ingredients and provides new ideas for exploring targeted therapies for specific Enteropathogens. Graphical Abstract Graphical  illustration for construction of self-assembly nanoprodrugs PPRG and its antibacterial and anti-inflammatory activities on experimental Salmonella infection in mice